Effectiveness of Peppermint Aromatherapy to Reduce Nausea and Vomiting in Pregnant Women in The First Trimester - Winengsih, Neneng; Triana, Triana; Choirunissa, Risza (Open Access Health Scientific Journal, 2026)
Background: Emesis gravidarum is a condition of severe nausea and vomiting in pregnant women in the first trimester that can cause serious complications such as dehydration and nutritional disorders. At the Jatibaru Health Center, Subang Regency, complaints of nausea and vomiting in the first trimester have increased, but effective non-pharmacological treatment is still limited. Peppermint aromatherapy, with its antiemetic menthol content, has been widely researched as a safe and effective therapeutic alternative to reduce these symptoms. This study aimed to evaluate the effectiveness of peppermint aromatherapy in reducing the rate of nausea and vomiting in pregnant women in the first trimester.Methods: The study used a quasi-experimental design with a pretest-posttest group control approach. A sample of 54 first-trimester pregnant women was divided into a treatment group (n=27) that received peppermint aromatherapy twice daily for seven days, and a control group (n=27) without intervention. Data were collected using the PUQE (Pregnancy Unique Quantification of Emesis) Score and analyzed univariate and bivariate using Wilcoxon and Mann-Whitney tests.Results: The average PUQE score of the treatment group decreased significantly from 10.56 (SD=1.188) to 5.33 (SD=1.038) after the intervention (p=0.000). The control group also experienced a decrease in score from 11.04 (SD=0.759) to 9.96 (SD=0.808) (p=0.000), but this decrease was smaller than that of the treatment group. Intergroup analysis showed a significant difference in the decrease in PUQE score (p=0.000), proving the effectiveness of peppermint aromatherapy in reducing symptoms of emesis gravidarum.Conclusion: Peppermint aromatherapy is effective in significantly reducing the rate of nausea and vomiting in pregnant women in the first trimester at the Jatibaru Health Center, Subang Regency. This therapy can be a safe and practical non-pharmacological alternative to improve the comfort of pregnant women